Local homicides increase suicide in US counties - Semenza, Daniel C.; Thomas, Christopher; Stansfield, Richard; Johnson, David B.; Burke, Kimberly C.; Anestis, Michael D. (Social science & medicine (1982), 2025)
Suicide remains a leading cause of death in the United States, with rates rising over the past two decades. While research suggests an association between exposure to interpersonal violence and suicide risk, few studies have examined this relationship at the macro level using longitudinal data and quasi-experimental methodologies. This study analyzes the longitudinal relationship between homicide and suicide rates across U.S. counties from 1968 to 2019, with a focus on variation by race, firearm involvement, and urbanicity. Using a quasi-experimental System Generalized Method of Moments (GMM) approach to address endogeneity and reverse causality, the study examines 162,472 county-year observations from the CDC WONDER database and the National Historical Geographic Information System. Findings indicate that higher homicide rates predict subsequent increases in suicide rates one year later, particularly for firearm-related fatalities. A one-unit increase in the total homicide rate was associated with a 0.493-unit increase in total suicide rates (95 % CI: 0.372, 0.614, p < .001). The homicide-suicide relationship was stronger among White populations and in rural areas. These results underscore the interconnectedness of interpersonal and self-directed violence, emphasizing the need for suicide prevention strategies that incorporate community-wide violence reduction efforts. •Higher homicide rates predict increased suicide rates in US counties over five decades.•Firearm-related homicides have stronger associations with suicide than non-firearm homicides.•Effects vary by race, with White populations showing larger and more consistent increases in associated suicide risk.•Urban-rural disparities reveal stronger homicide-suicide associations in rural counties.•Findings underscore the need for violence reduction as a suicide prevention strategy.